THE IMPACT OF AUTHENTIC LEADERSHIP ON EMPLOYEE CREATIVITY MEDIATED BY AFFECTIVE COMMITMENT (STUDY AT PT. UBA UHUD INTERNATIONAL) - Pratama, Angga Ardiansyah; Prayogi, Joni (REVENUE: Jurnal Manajemen Bisnis Islam, 2024)
This study aims to analyze the effect of Authentic Leadership on Employee Creativity with the mediation of Affective Commitment at PT Uba Uhud International in Cilacap. The dependent variable used in this study is Employee Creativity, the independent variable is Authentic Leadership, and uses the mediating variable, namely Affective Commitment. The data collection technique used in this research is a questionnaire. The number of respondents taken in this study were 50 respondents. Purposive sampling method is used in determining respondents. Based on the results of research and data analysis using SPSS linear regression shows that: (1) Authentic Leadership has a positive effect on Employee Creativity, (2) Authentic Leadership has a positive effect on Affective Commitment, (3) Affective commitment has a positive effect on Employee Creativity, (4) Authentic Leadership has a positive effect on Employee Creativity mediated by Affective Commitment. The implication of the above conclusions is that the leadership of PT Uba Uhud is expected to increase knowledge and make considerations in strategies for implementing leadership styles in decision makers and can improve a comfortable work environment to increase employee creativity and to expand the global market for coconut fiber.